The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1159/000519245
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 on Blood Transfusion Services: A Systematic Review and Meta-Analysis

Abstract: Introduction: While SARS-CoV-2’s main transmission route is through respiratory droplets, research has found that viral RNA could be detected in blood samples, causing concerns over the safety of blood donations and blood products. This paper therefore aims to systematically search for studies that have addressed their country’s lack of donations and analyse the risk of blood transfusion-transmission. As such, it will answer the question “should blood services focus more on donation vigilance or worry more abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 58 publications
1
19
0
Order By: Relevance
“…The rRT-PCR analysis revealed that all of the tested donated blood samples were negative for SARS-CoV-2 RNA in the current study. This is consistent with two recent studies [ 27 , 28 ]. Owusu and his colleagues tested plasma from SARS-CoV-2 infected individuals in Ghana, but they found SARS-CoV-2 viral RNA in only 1.03% of the tested plasma samples, concluding that blood transfusion is negligible risk factor for SARS-CoV-2 transmission [ 27 ].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The rRT-PCR analysis revealed that all of the tested donated blood samples were negative for SARS-CoV-2 RNA in the current study. This is consistent with two recent studies [ 27 , 28 ]. Owusu and his colleagues tested plasma from SARS-CoV-2 infected individuals in Ghana, but they found SARS-CoV-2 viral RNA in only 1.03% of the tested plasma samples, concluding that blood transfusion is negligible risk factor for SARS-CoV-2 transmission [ 27 ].…”
Section: Discussionsupporting
confidence: 94%
“…Although coronaviruses typically infect the respiratory tract, viral shedding in serum or plasma is to be expected. This raises concerns about the safety of donated blood products, because it is primarily dependent on voluntary blood donors [ 27 , 28 ]. Given the increasing number of asymptomatic [ 11 , 12 , 13 ] and reactivated SARS-CoV-2 cases [ 14 , 15 ], blood safety and coronaviruses should be prioritized, particularly in high-risk areas [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With evidence that severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is transmissible by asymptomatic individuals and the majority of the individuals being asymptomatic, a threat to blood supply was looming large. While elective procedures were put on hold to deal with the unprecedented crisis in hospitals, shortages of blood for emergencies and multi-transfused patients were reported from major healthcare centres across many countries [1] .…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review on the impact of COVID-19 on blood transfusion services revealed a 38% decrease in blood donation compared to the prepandemic period (Chiem et al, 2021). Chandler et al (2021) surveyed 1205 European blood donors and found a decrease in the frequency of blood donation and a reduced likelihood to donate in donors with higher adherence to COVID-19 preventive measures.…”
Section: Introductionmentioning
confidence: 99%